Nasionalisme Religius dan Transformasi Etnis: Analisis Sosiologis Identitas Melayu - Amalia Irfani; Patmawati Patmawati; Elmansyah Elmansyah; Julio Tomas Pinto; Al Fakhri Zakirman (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2026)
Malay as a “nation” in Asia is now no longer seen as having a central role in the development of a country, as happened in the 20th century, where Indonesia, Malaysia, Singapore, Thailand and Brunei Darussalam became evidence of their contribution to the formation of countries in Southeast Asia. It raises a big question: What is actually happening to the Malay ethnic group today? This study attempts to look at the development of the Malay ethnic group in the Southeast Asian region from a communal historical perspective. The method used in this study is a descriptive qualitative method with a historical approach. Based on the results of a critical analysis of historical data on the distribution of the Malay ethnic group in Southeast Asia, several conclusions were found, namely: 1) The Malay ethnic group is a unique ethnic group and has a vital role in the Southeast Asian region about the formation of national and state nationalism; 2) post-colonial, the Malay ethnic group has merged into various countries in Southeast Asia (Indonesia itself as its country of origin, Malaysia, Singapore, Brunei, and Thailand, as well as in the Philippines), as part of ethnic nationalism; 3) Until now, several countries have tried to make the Malay ethnic group their national identity, such as Malaysia, Singapore and Brunei Darussalam.